Routledge handbook of judicial behavior - Howard, Robert M.; Randazzo, Kirk A. (Routledge handbooks, 2018)
"Interest in social science and empirical analyses of law, courts and specifically the politics of judges has never been higher or more salient. Consequently, there is a strong need for theoretical work on the research that focuses on courts, judges and the judicial process. The Routledge Handbook of Judicial Behavior provides the most up to date examination of scholarship across the entire spectrum of judicial politics and behavior, written by a combination of currently prominent scholars and the emergent next generation of researchers. Unlike almost all other volumes, this Handbook examines judicial behavior from both an American and Comparative perspective.?Part 1 provides a broad overview of the dominant Theoretical and Methodological Perspectives used to examine and understand judicial behavior,Part 2 offers an in-depth analysis of the various current scholarly areas examining the U.S. Supreme Court,Part 3 moves from the Supreme Court to examining other U.S. federal and state courts, andPart 4 presents a comprehensive overview of Comparative Judicial Politics and Transnational Courts.Each author in this volume provides perspectives on the most current methodological and substantive approaches in their respective areas, along with suggestions for future research. The chapters contained within will generate additional scholarly and public interest by focusing on topics most salient to the academic, legal and policy communities."--Provided by publisher